2021
DOI: 10.3390/dj9060072
|View full text |Cite
|
Sign up to set email alerts
|

External Root Resorption Management of an Avulsed and Reimplanted Central Incisor: A Case Report

Abstract: Background: Avulsion and reimplantation of permanent teeth represent a major challenge in terms of treatment and long-term prognosis. The present study reported clinical management of external root resorption of an avulsed and reimplanted maxillary central incisor. Case report: A 9-year-old boy reported an uncomplicated crown fracture and avulsion of tooth 11 and complicated crown fracture of tooth 21 due to trauma. Reimplantation of element 11 was obtained within 30 min post-trauma and 3 days after both eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Several physical activities present a possible risk of maxillofacial injuries due to (1) falls and (2) collisions with other players, hard surfaces, and solid objects [ 23 , 24 , 25 ]. Although the importance of wearing a mouthguard is paramount as a preventive measure, the athlete does not always wear it, or wears it improperly [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physical activities present a possible risk of maxillofacial injuries due to (1) falls and (2) collisions with other players, hard surfaces, and solid objects [ 23 , 24 , 25 ]. Although the importance of wearing a mouthguard is paramount as a preventive measure, the athlete does not always wear it, or wears it improperly [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several physical activities present a possible risk of maxillofacial injuries due to (1) falls and (2) collisions with other players, hard surfaces, and solid objects [ 23 , 24 , 25 ]. Although the importance of wearing a mouthguard is paramount as a preventive measure, the athlete does not always wear it, or wears it improperly [ 24 , 25 , 26 ]. Usually, the most common reasons for not wearing a mouthguard are discomfort and difficulty with breathing, talking, and swallowing, during an activity [ 24 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most often, the phenomenon initially reveals itself with small-sized lesions of cementum within PDL and, if not treated, may progress towards the involvement of the dental pulp [ 5 ]. Traumatic injuries, replantation of avulsed teeth, intentional (auto)replantation, and autogenous tooth transplantation are amongst factors that could initiate EIRR [ 6 ]. Since EIRR is a deteriorating lesion and could end in the gradual destruction of dental structure and subsequent tooth loss [ 7 ], it should be immediately diagnosed, properly managed, and perfectly treated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has claimed that regenerative endodontic procedures (REPs) can be elaborated as a potential solution for the treatment of EIRR; however, REPs are not contemplated as the first treatment option and need further clinical trials [ 9 ]. Nonetheless, it has been shown that immediate endodontic treatment and removal of microorganisms accompanied by the application of a suitable calcium silicate-based biomaterial could arrest and contrast the advancement of root resorption in reimplanted and avulsed teeth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%